Star‐Shaped Phenylene BODIPY: Synthesis, Properties and Biocompatibility Assessment Using Zebrafish. Issue 28 (24th July 2020) - Mahanta, Chandra Sekhara; Aparna, Sai; Das, Saroj Kumar; Jena, Bibhuti Bhusan; Swain, Biswa Ranjan; Patri, Manorama; Dash, Barada P.; Satapathy, Rashmirekha
Abstract: A C3 ‐symmetrical star‐shaped phenylene core based borondipyrromethene (BODIPY) has been synthesized and its toxicity and biocompatibility has been evaluated using a vertebrate model, zebrafish. The BODIPY has been found to absorb and emit in solution and solid state between 450 nm‐700 nm. It has been found to be non toxic in adult zebrafish model up to concentration 100 mg/L. The neurobehavioral alterations and bioimaging properties of the BODIPY in zebrafish adults and embryos have also been investigated. The dose‐response study of BODIPY 6 was carried out by light and dark preference test (LDPT) and novel tank diving test (NTDT) to observe behavioral alteration in adult zebrafish. The LDPT showed that time spent in light zone and number of transition to light zone rose up to administration of 6.8 mg/L BODIPY where as latency towards light zone remarkably decreased at concentration 6.8 mg/L. The NTDT test followed similar trend and the number of transitions and time spent in top zone increased in accordance to BODIPY treatment concentration where as latency towards top zone decreased gradually. The phenylene BODIPY was accumulated into and bound to different parts of zebrafish larvae. Our results indicate that the star shaped phenylene cored compound containing multiple BODIPY moieties exhibits no toxicity and also shows good biocompatibility and biodistribution in zebrafish and thus it may find promising biological applications. Abstract : A star‐shaped phenylene borondipyrromethene (BODIPY) has been synthesized and its toxicity and biocompatibility has been evaluated using a vertebrate model, zebrafish. The neurobehavioral alterations and bioimaging properties of the BODIPY in zebrafish adults and embryos have also been investigated.